Pengaruh Kenaikan Harga Tahu Terhadap Minat Beli Masyarakat Di Kota Bima - Muhammad Ikraman; Sri Ernawati (Universitas Mataram, 2020)
In a factory, to provide a decision regarding product pricing is very important and not easy to do. Changes in prices that are very small or very large will cause significant impacts and changes to sales in a large enough quantity, so if there is a mistake in determining the selling price, the company will lose or lose customers because the specified selling price is too low or too high. from this study was to determine the effect of rising prices Interest of Buying in the city of Bima. This type of research is associative with the type of quantitative data from primary data sources. The study population is all people in the Bima City who have bought tofu products. Sampling of this study using a purposive sampling technique. Data analysis techniques used are validity and reliability, simple linear regression analysis, correlation coefficient, coefficient of determination (R2) and t test. Data processing and analysis was carried out using the Statistical Product and Service Solution (SPSS) program version 21.0. The results of this study prove that there is no effect of tofu price increase on people's Interest of Buying in the Bima City.